Better safe than sorry: TOB1 employs multiple parallel regulatory pathways to keep Th17 cells quiet. (19th February 2014) - Salerno, Fiamma; van, René A. W.; Wolkers, Monika C.
<x xml:space="preserve">Abstract</x> Th17 cells are key players in antibacterial and antifungal immunity, but have also been implicated in autoimmunity. Interestingly, Th17 cells poorly proliferate upon stimulation, a phenotype that was attributed to a decreased sensitivity to T‐cell receptor (TCR) stimulation, and to low IL‐2 production by Th17 cells. In this issue of the European Journal of Immunology, Santarlasci et al. [Eur. J. Immunol. 2014. 44: 654–661] shed further light on the molecular mechanism that keeps Th17 cells at bay. They identify the transcriptional regulator TOB1, which not only impairs IL‐2 production in Th17 cells, but also blocks the expression of cell cycle genes. Strikingly, TOB1 suppresses Th17‐cell proliferation through several pathways, including impaired signal transduction, transcription, and possibly also post‐transcriptional regulation.